Efficient deep learning-based tomato leaf disease detection through global and local feature fusion - Hao Sun; Rui Fu; Xuewei Wang; Yongtang Wu; Mohammed Abdulhakim Al-Absi; Zhenqi Cheng; Qian Chen; Yumei Sun (BMC Plant Biology)
Abstract In the context of intelligent agriculture, tomato cultivation involves complex environments, where leaf occlusion and small disease areas significantly impede the performance of tomato leaf disease detection models. To address these challenges, this study proposes an efficient Tomato Disease Detection Network (E-TomatoDet), which enhances tomato leaf disease detection effectiveness by integrating and amplifying global and local feature perception capabilities. First, CSWinTransformer (CSWinT) is integrated into the backbone of the detection network, substantially improving tomato leaf diseases’ global feature-capturing capacity. Second, a Comprehensive Multi-Kernel Module (CMKM) is designed to effectively incorporate large, medium, and small local capturing branches to learn multi-scale local features of tomato leaf diseases. Moreover, the Local Feature Enhance Pyramid (LFEP) neck network is developed based on the CMKM module, which integrates multi-scale features across different detection layers to acquire more comprehensive local features of tomato leaf diseases, thereby significantly improving the detection performance of tomato leaf disease targets at various scales under complex backgrounds. Finally, the proposed model’s effectiveness was validated on two datasets. Notably, on the tomato leaf disease dataset, E-TomatoDet improved the mean Average Precision (mAP50) by 4.7% compared to the baseline model, reaching 97.2% and surpassing the advanced real-time detection network YOLOv10s. This research provides an effective solution for efficiently detecting vegetable pests and disease issues.